ALGORITMA PEMILIHAN DIAMETER PAHAT PROSES PEMESINAN POCKET 2-1/2D DENGAN METODA HIGH SPEED MACHINING - Nurkertamanda, Denny
Many researches in tool diameter chosen for pocket 2-1/2D machining process have been done, such as research that looked for multitools diameter to the process prismatic pocket 2-1/2D by using Voronoi mountain concept (Veermani and Gau, 2000). The other war research model for selecting single tool by Yao, et al. (2001) where tool diameter size is defined by work pieces geometric form. Both researches were based on machining process that use conventional machine method, and only discussed about how to remove as many as material can be in pocket form process. This research develops a model for selecting single tool by Yao, et al. (2001), so that the model can be applied in 2-1/2D pocket machining process using high speed machining (HSM) method with trochoidal tool path machining. The model also considers the roughness of product's total finish surface to define multi or single tool diameter. For model comparison, model for selecting single tool by Yao is also developed by considering product's surface roughness for conventional machining process with contour-offset tool path, inside to outside cutting process. The comparison shows that HSM method in average 65.3% faster than conventional machining method for the same work piece.